Enhancement of Naphthalene Degradation by a Sequential Sulfate Injection Scenario in a (Semi)-Arid Coastal Soil: a Flow-Through Reactor Experiment - Saeid Shafieiyoun (14151654) (2022)
Engineered sulfate injection has been introduced as an effective technology to enhance the remediation of soil and groundwater contaminated by petroleum hydrocarbons. While some studies indicate that sulfate injection is a promising method for the treatment of hydrocarbon-contaminated subsurface systems, its application in the brackish soil environments is unknown. In this study, we explored related geochemical indicators along with soil adsorption and dissolved phase concentrations to provide an improved understanding of the hydrocarbon-contaminated subsurface responses to the sulfate injection in brackish environments. A series of flow-through experiments representing in situ groundwater anaerobic bioremediation were conducted and two sulfate injection episodes were applied to examine the degradation of dissolved naphthalene under low salinity and brackish conditions. As opposed to the substantial body of previous studies that salinity restricts biodegradation, the results from this study showed that naphthalene anaerobic degradation was more stable once the salinity was as high as that at the sampling location in the coastal brackish environment. While increasing naphthalene concentration from 4 to 12 mg L−1 did not limit biodegradation efficiency under brackish condition similar to the sampling location, it adversely restricted the developed reducing conditions and biodegradation process under low salinity conditions. This highlights the adaption of the microbial communities within the soil to the brackish environment at the sampling location suggesting that changing the salinity during engineered sulfate application can make the remediation process more susceptible against the environmental stresses and substrate toxicity. The results of this study provide insight into the engineered sulfate application as a remediation strategy for potential removal of dissolved naphthalene from the contaminated brackish groundwater. Other Information Published in: Water, Air, & Soil Pollution License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s11270-020-04725-5